An alternative aerosol delivery system for amiloride. - Everard, M. L. (1995)
BACKGROUND--The advent of novel treatments such as aerosolized amiloride are potentially useful additions to the therapeutic options available for the treatment of cystic fibrosis. Unfortunately, amiloride and other aerosolized drugs such as antibiotics are generally administered via jet nebulisers which are time consuming to use, and thus limit the acceptance and efficacy of these forms of treatment. In vitro experiments were performed in order to determine whether amiloride could be administered in dry powder form using a Turbohaler. METHODS--Amiloride was micronised and loaded into 200 micrograms Turbohalers. The dose delivered per actuation and particle size distribution of the generated aerosol were assessed using a flow of 60 l/min through the Turbohaler. The dose of amiloride delivered was measured by collecting the aerosol on a filter and the quantity of drug was assayed by an ultraviolet spectrophotometric method. The particle size distribution was assessed using a Malvern MasterSizer laser particle sizer and compared with that generated by a commercially available 200 micrograms budesonide Turbohaler. RESULTS--The mean (SD) dose delivered per actuation was 246.3 (40.4) micrograms. The volume median diameter of the amiloride aerosol was 3.80 (0.68) micron compared with 3.07 (1.47) microns for budesonide. CONCLUSIONS--These results suggest that therapeutic doses of micronised amiloride could be delivered effectively and conveniently as a dry powder aerosol using a Turbohaler.